Managing Climate Change. Climate, Growth and Equitable Development - Nicholas Stern (Collège de France, 2010)
Climate change has been the source of immense challenges for ethical, economic or political analysts. We are aware of the scale of the action required to be taken and the areas in which that action is needed namely efficient energy use, low carbon technologies or deforestation. We have an idea of which technologies need to be developed. We understand the basic economic policy incentives in favour of reducing emissions, stopping deforestation and promoting more sensible use of our natural envi...